Critiquing Metanarratives through Historiographic Metafiction in Graham Swift’s Last Orders - Khanal, Ananta (SCHOLARS: Journal of Arts & Humanities, 2025)
Graham Swift’s Last Orders, a novel set in late twentieth-century England, explores postmodern tensions surrounding history and mortality by primarily focusing on the personal narratives of four working-class men—Ray, Vic, Lenny, and Vince—in the aftermath of Jack Dodds’s death. This article examines how the intertwined memories of those characters exteriorize fragmented and subjective histories that challenge traditional metanarratives, particularly those rooted in colonial and nationalist ideologies. Drawing on theories of historiographic metafiction, this qualitative and text-based analysis highlights the novel’s self-reflexive and intertextual form to show how the narrative resists the notion of death as narrative closure and history as a singular and objective truth. Based on the features employed in the novel, I argue that the novel critiques the dominant metanarratives embedded in humanism, Christianity, and colonial legacies. Thus, this article contributes to broader discussions in literary and cultural studies about how the narrative reimagines the past and questions official histories through individual and localized perspectives.